Strengthening the Solidarity Through Social Media Networks in Communities at the Ciliwung Riverbank - Irwan, Irwan; Kolopaking, Lala M.; Muljono, Pudji; Yonvitner, Yonvitner (Komunitas, 2019)
In general, the focus of this study analyzes the strengthening of solidarity through social media networks in communities living in the Ciliwung River Basin. There are two objectives of this study, namely analyzing social media can strengthen the solidarity and the forms of solidarity that are built on the community affected by floods and landslides in the Ciliwung River Basin. This research was conducted in a community that resides in the Ciliwung River, Kedunghalang Village, North Bogor District, Bogor City. Theoretical analysis uses social media theory from VanDijk and the theory of solidarity from Durkheim. Data collection techniques were carried out by non-participant observation, and in-depth interviews. The data analysis technique was carried out by the Milles and Huberman analysis model among neigboarhoods (RT) and hamlet/groups of neighboarhoods (RW) level. The results of the study show that social media is able to strengthen community solidarity in the Ciliwung Riverbank, a disaster prone area. Solidarity built through social media are social relations, social norms and inter-household trust. Social relations built on social media networks at the level of individuals and groups are high. The form of built solidarity is mechanical solidarity that has a strong collective awareness, trust and mutual assistance. The novelty of this research shows that social media network is able to form social relations in strengthening solidarity.